Genome-wide association study identifies five new schizophrenia loci. - MORRIS, DEREK; CORVIN, AIDEN PETER; GILL, MICHAEL; DONOHOE, GARY (JAMES) (My University, 2011)
We examined the role of common genetic variation in schizophrenia in a genome-wide association study of substantial size: a stage 1 discovery sample of 21,856 individuals of European ancestry and a stage 2 replication sample of 29,839 independent subjects. The combined stage 1 and 2 analysis yielded genome-wide significant associations with schizophrenia for seven loci, five of which are new (1p21.3, 2q32.3, 8p23.2, 8q21.3 and 10q24.32-q24.33) and two of which have been previously implicated (6p21.32-p22.1 and 18q21.2). The strongest new finding ( P = 1.6 ? 10 ? 11 ) was with rs1625579 within an intron of a putative primary transcript for MIR137 (microRNA 137), a known regulator of neuronal development. Four other schizophrenia loci achieving genome-wide significance contain predicted targets of MIR137 , suggesting MIR137 -mediated dysregulation as a previously unknown etiologic mechanism in schizophrenia. In a joint analysis with a bipolar disorder sample (16,374 affected individuals and 14,044 controls), three loci reached genome-wide significance: CACNA1C (rs4765905, P = 7.0 ? 10 ? 9 ), ANK3 (rs10994359, P = 2.5 ? 10 ? 8 ) and the ITIH3-ITIH4 region (rs2239547, P = 7.8 ? 10 ? 9 ).
PUBLISHED
Keywords: Psychiatry